Beyond stress and coping: the relevance of critical theoretical perspectives to conceptualising racial discrimination in health research. Issue 3 (2nd September 2019) - Varcoe, Colleen; Browne, Annette; Blanchet Garneau, Amélie
ABSTRACT: Racial discrimination is primarily conceptualised and dealt with at the individual level in health research and practice. Most conceptualisations, and the measures which follow, are grounded in stress-coping theories thus reinforcing individual level understandings. This draws attention away from how structures and systems reproduce racial discrimination, and further supports the very racial categorisations upon which racism depends. The purpose of this paper is to discuss the relevance of critical theoretical perspectives in conceptualising racial discrimination and how it is taken-up and measured in health research. Drawing on Indigenous, Black and material feminist, intersectional, critical race, postcolonial and political economy perspectives, we propose that racial discrimination can most usefully be understood as a relational socio-historical concept. Racial discrimination understood at the systemic level in research and measurement will support more effective policies and practices to mitigate intersecting forms of discrimination in healthcare. Critical theoretical approaches to studying racial discrimination in health research could inform future analyses needed to address and limit the harms perpetuated through individual and structural forms of discrimination.